2023
DOI: 10.3390/electronics12183790
|View full text |Cite
|
Sign up to set email alerts
|

Data Rate Selection Strategies for Periodic Transmission of Safety Messages in VANET

Ben St. Amour,
Arunita Jaekel

Abstract: Vehicular ad hoc networks (VANETs) facilitate communication among vehicles and possess designated infrastructure nodes to improve road safety and traffic flow. As the number of vehicles increases, the limited bandwidth of the wireless channel used for vehicle-to-vehicle (V2V) communication can become congested, leading to packets being dropped or delayed. VANET congestion control techniques attempt to address this by adjusting different transmission parameters, including the data rate, message rate, and transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…0, rss j ≤ rss min , rss j −rss min rss max −rss min , rss min < rss j < rss max , 1, rss j ≥ rss max , (10) where rss min and rss max are the minimum and maximum thresholds of RSS for not being able to receive and guaranteed to receive safety messages, respectively.…”
Section: Data Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…0, rss j ≤ rss min , rss j −rss min rss max −rss min , rss min < rss j < rss max , 1, rss j ≥ rss max , (10) where rss min and rss max are the minimum and maximum thresholds of RSS for not being able to receive and guaranteed to receive safety messages, respectively.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…The Vehicular Ad Hoc Network (VANET) has emerged as a cornerstone for Intelligent Transportation Systems (ITSs), offering a promising solution to these challenges [1]. VANET has garnered extensive research attention and has found applications in signal control [2,3], route optimization [4,5], cooperative tasks [6][7][8], and safety communication [9,10], among others. Particularly, VANET has significant research merit and practical value in safety communication.…”
Section: Introductionmentioning
confidence: 99%